Analysis of Blood Flow Characteristics in a Model of a Mature Side‐to‐Side Arteriovenous Fistula. Issue 11 (21st March 2017) - Javadzadegan, Ashkan; Myo Lwin, Nay; Asyraf, Muhammad; Simmons, Anne; Barber, Tracie
Abstract: The creation of an arteriovenous fistula (AVF) is a common surgical procedure in hemodialysis patients suffering from end‐stage renal disease (ESRD). However, several complications may occur after surgery, including thrombosis, stenosis, and aneurysm. These complications are attributed to hemodynamics perturbations including pathophysiological wall shear stress (WSS) and flow recirculation zones. In this study, we present a computational hemodynamic analysis in a model of a mature side‐to‐side AVF, which is then validated by experimental measurements. Both computational and experimental results confirmed the presence of complex flow patterns within the AVF with vortices initially developing at the center of the venous region and gradually moving downstream, such that at four characteristic anastomosis lengths downstream, the flow disturbances became minimum. A complex pattern was also observed in WSS distribution with regions of low and high WSS identified in proximal vein and feeding artery, respectively. In addition, the temporal distribution of WSS varied significantly along the venous wall where a large portion of it remained above normal levels of WSS during systole while the area was largely normal during diastole. Our findings support the hypothesis that high WSS is not detrimental to immediate patency of AVF; however, other factors including low WSS and temporal and spatial gradients of WSS increase the risk of vascular access complications.